2009
DOI: 10.1111/j.1551-2916.2008.02900.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Large‐Scale YBa2Cu3O7−x Superconductor Prepared by Plastic Forming without a High‐Pressure Molding: Effect of Polyvinyl Alcohol (PVA) Addition on the Superconducting Properties

Abstract: The preparation of large‐scale YBa2Cu3O7−x superconductor samples was investigated. This method is based on plastic forming using a slurry consisting of YBa2Cu3O7−x particles and a sol solution made up of multimetallic hydroxide particles (YBa2Cu3(OH)x colloidal particles) and poly(vinyl) alcohol (PVA). The effects of adding PVA on the product, the crystallinity, and the superconducting properties of the sample were investigated. It was found that PVA acted as a protective colloid in the sol solution and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The preparation procedure for the YBCO bulk samples is described in our previous studies . The YBCO powder was made in two ways, using a sintering method and a melt‐texturing method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation procedure for the YBCO bulk samples is described in our previous studies . The YBCO powder was made in two ways, using a sintering method and a melt‐texturing method.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we reported that a large sample of YBCO material (80 mm × 80 mm × 3 mm) can be easily produced by plastic‐forming method using a slurry that consists of YBCO particles and YBa 2 Cu 3 (OH) y multimetallic hydroxide colloidal particles that act as an inorganic binder, with polyvinyl alcohol (PVA) acting as a dispersant or protective colloid . When the preparation conditions (such as the PVA concentration, firing temperature, and firing time) were optimized, the J c of the YBCO samples was 755 ± 135 A/cm 2 at 77 K on average; after oxygen annealing at 773 K for 10 h, the average J c became 2300 A/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The formability of materials is important in fabricating Ca 3 Co 4 O 9 ceramic products, such as thermoelectric conversion elements. Therefore, we developed a plastic forming method to form ceramics directly for manufacturing large oxide superconductors . A clay‐like precursor is prepared by mixing an oxide powder as a base material and a binder, and this precursor is formed into the desired shape and fired to produce ceramics of various shapes easily.…”
Section: Introductionmentioning
confidence: 99%
“…Sol solutions were prepared by suspending the refined precursor in the solution at various PVA concentrations using an ultrasonic cleaner. PVA with an average molecular weight of 22 000 (degree of polymerization5500) was dissolved in warm water (at 40 -45°C) and the solution was equilibrated to room temperature [8]. Green sheet samples (about 80 mm x 80 mm x 3 mm) were made using the slurry prepared by mixing 10 g of YBa 2 Cu 3 O 7-x powder (average diameter 0.15 mm) and 3 ml of 0.05 mol/dm 3 precursor solution (average diameter of precursor particle: 380 nm) (kneading time: 50-60 min).…”
Section: Introductionmentioning
confidence: 99%